ORAL TOXICITY STUDY OF THE VENOM OF NAJA NAJA IN ALBINO RATS - M. MALLESWARI; SACHI DEVI.P; S.V. RAVIKANTH; P. JOSTHNA; P. JACOB DOSS (International Journal of Pharma and Bio Sciences, 2014)
The venom of Naja naja has been studied clinically as an analgesic. It has been recently determined that the venom of cobra is biologically active even when it is administered by mouth. As there are no published studies on the effects of orally administered cobra venom, a 72h toxicity study was conducted in the Albino rats. We have selected 1/50th LD50 dose (7µg/ kg body weight) in the present investigation and this dose was administered intragastrically. Group I (24h) received single dose, Group II (48h) received 2 doses with an interval of 24h and Group III (72h) received 3 doses daily with an interval of 24h. At the end of the experiment (i.e. 24h after administration of venom) the animals were sacrificed and the blood was examined. The alterations in the haeomogram after envenomation are of vital importance. The present study is aimed to investigate whether oral administration of venom damages gut lining and escapes into the blood stream and cause damage to the animals as seen in regular bites. The examination of various parameters demonstrates that cobra venom when administered orally at low doses is toxic to the animals. In the present study oral administration of snake venom severely altered all the parameters indicating that oral administration is also as toxic as compared to the injected venom. Snake venom is dangerous and should be treated with extreme caution and not ingested in any form.